Epidural Anesthesia in Management of Pregnant Eissenmenger’s Syndrome Patient Undergoing Caesarean Section - Jayantha Ananda, I Gusti Ngurah Bagus; Tjahya Aryasa; Tjokorda Gde Agung Senapathi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Eisenmenger syndrome is very rare in pregnant women. Debates remain concerning the management of Eisenmenger syndrome in this patient population, and the prognosis is unclear in terms of maternal and fetoneonatal outcomes. Managing anesthesia in maternal patients with a cardiac abnormality might be particularly difficult because these individuals have inadequate circulatory reserves and altered maternal cardiovascular physiology. Case presentation: We present a 26-year-old 34 weeks pregnant woman with Eisenmenger’s syndrome (ES) scheduled for an elective caesarean section. The clinical findings reveal slight tachypnea with peripheral oxygen saturation of 82% with oxygen supplementation using a cannula at 3 lpm. The patient's baseline hemodynamics are stable, but a third-degree murmur is heard in the 3rd and 4th left intercostal space. The patient was managed with epidural anesthesia using bupivacaine 0.5% 20 ml without adjuvant. The epidural catheter was inserted in an interspinous process between L3-L4. The surgery was done in 90 minutes with stable hemodynamics, and postoperatively, the patient was monitored in the intensive cardiac care unit (ICCU). Conclusion: Epidural anesthesia has been shown to provide favorable outcomes due to its slow onset and reducing the likelihood of abrupt hemodynamic changes.